The Portrayal of Marginalized Masculinity and Patriarchy in Laila Lalami’s Hope and Other Dangerous Pursuits - Lubis, Adek Suryani; Az Zahra, Fatimah; Azzahra, Sayyidati (Fakultas Adab dan Humaniora, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2024)
This paper aims to explore the phenomenon of gender discourse depicted through the stories of Moroccan immigrants in Laila Lalami's Hope and Other Dangerous Pursuits (2005). In detail, this paper will discuss the subordinate of masculinity and the patriarchal system's oppression of Muslim women with Walby’s theory of patriarchy (1990). Walby defined patriarchy as a system of male-dominated societal structures and behaviors that subjugate women. This researcher uses the qualitative descriptive method to conduct scientific data analysis in order to interpret surrounding phenomena. It also focuses on challenging gender bias by utilizing the concepts of feminism through the lives of imprisoned female characters and the subordinate of masculinity in male characters. From this research, the researchers draw the result that patriarchal culture creates tension between the roles of men and women, where men's masculinity becomes marginalized due to their inability to meet society's demands and standards. On the other hand, women also become victims of the way men gain recognition from the standards imposed on them.